Microstructural characterisation and mechanical properties of dissimilar AA5083-copper joints produced by friction stir welding - Gihad Karrar; Alexander Galloway; Athanasios Toumpis; Hongjun Li; Fadi Al-Badour (Journal of Materials Research and Technology, 2020)
This work aims to study the influence of the tool rotational speed and tool traverse speed on dissimilar friction stir butt welds on 3 mm thick AA5083 to commercially pure copper plates. Complex microstructures were formed in the thermo-mechanically affected zone, in which a vortex-like pattern and lamellar structures were found. Several intermetallic compounds were identified in this region, such as Al2Cu, Al4Cu9 and these developed an inhomogeneous hardness distribution. The highest ultimate tensile strength of 203 MPa and joint efficiency of 94.8% were achieved at 1400 rpm tool rotational speed and 120 mm/min traverse speed. Placing the softer material (aluminium) on the advancing side produced an excellent metallurgical bond with no requirement for tool offsetting.